Environmental Boundary Spanning and Information Processing Effects on Organizational Performance - Dollinger, Marc (Academy of Management Journal, 1984)
The boundary spanning activity of the entrepreneur is used to examine the strategic management process in small business. In a sample of 82 owner/operators, intensive boundary spanning activity was strongly related to organizational performance, and information processing capability significantly affected the performance-boundary spanning relationship.